KHALIFAH, AMIR AL-MUKMIN, IMAM, RA’IN: TINJAUAN BAHASA DAN ISTILAH DALAM PENGEMBANGAN KEPEMIMPINAN PENDIDIKAN ISLAM - Siti Urlan Agustina (Yayasan Baitul Hikmah al-Zain, 2025)
Leadership in Arabic is called khilafah, imarah, ziamah, and imamah. Etymologically, leadership means the style of leadership or the quality of a leader or the act of leading itself. While in terminology there are several definitions of leadership. Basically, all humans are God's caliphs who have equality in this caliphate. There is no division of groups based on differences in birth and social status. Everyone has the same position and status. The criteria that are prioritized to become a leader are personal ability and character. There are four words to refer to a leader, namely, Caliph, Amir Al-Mukmin, Imam and Ra'in. This paper uses a qualitative descriptive method with a type of research in the form of a literature study (library research), namely collecting information or scientific papers related to literature reviews that are library-based. This research was conducted by combining descriptive and qualitative research. This study also presents data without any manipulation or other additional treatments. The main source of this research is previous scientific papers that are closely related to the literature review, such as research method books, journal articles, internet articles, and other related writings. Leadership in Arabic is called khilafah, imarah, ziamah, and imamah. Etymologically, leadership means the style of leadership or the quality of a leader or the act of leading itself. While in terminology there are several definitions of leadership. There are four words to refer to a leader, namely, Khalifah, Amir Al-Mukmin, Imam and Ra'in. The four words will be explained in the following discussion.